DISEQUILIBRIUM MELT DISTRIBUTION DURING STATIC RECRYSTALLIZATION - Walte N.P.; Bons P.D.; Passchier C.W.; Koehn D. (My University, 2003)
Melt migration and segregation, and the rheology of partially molten rocks in the upper mantle and lower crust, strongly depend on the grain-scale distribution of the melt. Current theory for monomineralic aggregates predicts a perfectly regular melt framework, but high-temperature experiments with rock-forming minerals + melt show considerable deviations from this predicted geometry. Disequilibrium features, such as fully wetted grain boundaries and large melt patches, have been described; these were mainly attributed to surface-energy anisotropy of the minerals. We present static analogue experiments with norcamphor + ethanol that allow continuous in situ observation of the evolving liquid distribution. The experiments show that all previously reported disequilibrium features can form during fluid-enhanced static recrystallization when small grains are consumed. There is no need to invoke surface-energy anisotropy, although this might enhance the effect. All disequilibrium features are transitory and evolve back toward equilibrium geometry. However, because the system undergoes continuous static recrystallization, disequilibrium features are always present in a partially molten polycrystalline aggregate and therefore control its properties.
Keywords: analogue simulation; melts; porosity; permeability; norcamphor; recrystallization